2018
DOI: 10.1371/journal.pbio.2005281
|View full text |Cite
|
Sign up to set email alerts
|

The neurodevelopmental precursors of altruistic behavior in infancy

Abstract: Altruistic behavior is considered a key feature of the human cooperative makeup, with deep ontogenetic roots. The tendency to engage in altruistic behavior varies between individuals and has been linked to differences in responding to fearful faces. The current study tests the hypothesis that this link exists from early in human ontogeny. Using eye tracking, we examined whether attentional responses to fear in others at 7 months of age predict altruistic behavior at 14 months of age. Our analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 56 publications
(96 reference statements)
3
64
2
Order By: Relevance
“…Activations were observed in areas broadly consistent with previous adult fMRI studies, including temporal areas (Haxby et al, 2001), IFG (Sabatinelli et al, 2011), TPJ, and medial prefrontal SFG (Etkin, Egner, & Kalisch, 2011). Specifically, we found broad bilateral temporal and frontal responses to happy faces, in line with previous infant studies in which facial identity remained unvarying within each block (Grossmann et al, 2018;Krol et al, 2019;Minagawa-Kawai et al, 2009). Exploratory analyses of the current data revealed greater frontal (dSFG) activation to happy versus fearful faces, robust to changes in facial identity; this finding did not survive correction for multiple comparisons.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Activations were observed in areas broadly consistent with previous adult fMRI studies, including temporal areas (Haxby et al, 2001), IFG (Sabatinelli et al, 2011), TPJ, and medial prefrontal SFG (Etkin, Egner, & Kalisch, 2011). Specifically, we found broad bilateral temporal and frontal responses to happy faces, in line with previous infant studies in which facial identity remained unvarying within each block (Grossmann et al, 2018;Krol et al, 2019;Minagawa-Kawai et al, 2009). Exploratory analyses of the current data revealed greater frontal (dSFG) activation to happy versus fearful faces, robust to changes in facial identity; this finding did not survive correction for multiple comparisons.…”
Section: Discussionsupporting
confidence: 88%
“…Exploratory analyses of the current data revealed greater frontal (dSFG) activation to happy versus fearful faces, robust to changes in facial identity; this finding did not survive correction for multiple comparisons. At least one fMRI study in adults (Zhang et al, 2016) and another fNIRS study in infants (Grossmann et al, 2018) also do not report differential activations to different types of facial emotions over temporal cortices. Interestingly, and contrary to previous reports in behavioral and ERP paradigms Xie et al, 2018), no differences between 5-and 7-month-olds were found.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Identifying factors that contribute to variability in emotion processing in infancy is important to A C C E P T E D M A N U S C R I P T achieve a more mechanistic understanding of healthy and atypical socio-emotional development. In prior work, individual differences in emotion processing have been linked to overt social behaviors in neurotypical adults and infants [4,5], and have in more extreme forms been associated with a host of mental health disorders in adolescents and adults [6,7]. One factor that may contribute to variability in emotion processing is the endogenous oxytocin system.…”
Section: Introductionmentioning
confidence: 99%